A high wear resistance additively formed titanium matrix composite and method of making same

By depositing amorphous ceramic films on the surface of titanium alloy powder and generating nano-reinforcing phases through in-situ reaction, combined with additive manufacturing technology, the problem of insufficient wear resistance of titanium alloys was solved, and the preparation of high wear-resistant titanium-based composite materials was realized, which are suitable for aerospace and other fields.

CN121339431BActive Publication Date: 2026-03-20TIANMUSHAN LABORATORY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511940912.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-22
Publication Date
2026-03-20
Estimated Expiration
2045-12-22

AI Technical Summary

Technical Problem

The low hardness, poor wear resistance, and high coefficient of friction of titanium alloys limit their application in sliding and friction conditions. Furthermore, existing surface strengthening technologies are insufficient to achieve uniform coating coverage for complex-shaped components, leading to material surface failure.

Method used

By depositing amorphous ceramic films on the surface of titanium alloy powder, selective melting technology is used to induce in-situ reactions between titanium elements and B, C, or N elements in the amorphous ceramic films to generate nano-reinforcing phases (TiC, TiB, TiN) that are uniformly distributed within the titanium-based composite material. Combined with additive manufacturing technology, high wear-resistant titanium-based composite materials are prepared.

Benefits of technology

It significantly improves the wear resistance and overall performance of titanium alloys, making them suitable for use in extremely harsh working conditions. The material has strong fluidity and oxidation resistance, and the forming quality is high.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121339431B_ABST
    Figure CN121339431B_ABST
Patent Text Reader

Abstract

The application discloses a high-wear-resistance additive forming titanium-based composite material and a preparation method thereof. The high-wear-resistance additive forming titanium-based composite material is mainly composed of a matrix and an amorphous ceramic film, and the mass fraction of each component of the high-wear-resistance additive forming titanium-based composite material is as follows: the matrix is 97.0-99.8%, and the amorphous ceramic film is 0.2-3%. The application can realize the quantity and size regulation of the reinforcing phase by precisely controlling the thickness and mass of the amorphous ceramic film. The introduction of the amorphous ceramic film can significantly improve the flowability and oxidation resistance of the additive manufacturing titanium alloy powder. The in-situ self-grown ceramic reinforced titanium-based composite material prepared by additive manufacturing is crack-free, has high hardness and good wear resistance, and is suitable for use under harsh working conditions.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of additive manufacturing of titanium alloy materials, in particular to a high-wear-resistance additive forming titanium-based composite material and a preparation method thereof. BACKGROUND

[0002] Titanium alloy is widely praised as "space metal" and "ocean metal" due to its excellent specific strength and corrosion resistance. Its density is only 60% of that of steel, but its strength is comparable to that of high-strength steel. This characteristic makes it an ideal material for manufacturing landing gear, fuselage frame, compressor disc, rocket engine and fuel tank in the aerospace field, significantly reducing structural weight and improving fuel efficiency and payload. In marine engineering, titanium alloy shows excellent seawater corrosion resistance and is used for deep-sea submarine pressure hulls, ship propellers and seawater pipeline systems. In addition, it is also widely used in chemical industry, petroleum refining and seawater desalination, etc. for manufacturing reactors, heat exchangers and pipelines, greatly extending the service life of equipment and reducing maintenance costs. Titanium alloy also has excellent biocompatibility and has been successfully applied to medical implants such as artificial joints and dental implants, so it is also called "biological metal".

[0003] However, the inherent low hardness, poor wear resistance and high friction coefficient of titanium alloy limit its application in sliding, friction and other working conditions. The surface hardness of titanium alloy is low (usually only 30-35 HRC), much lower than that of tool steel or carburizing steel, which is prone to plastic deformation and scratches in friction. At the same time, titanium alloy has poor thermal conductivity, and friction heat is difficult to dissipate quickly, resulting in excessive local temperature rise, causing microstructure changes and exacerbating material adhesion tendency. More importantly, its high chemical activity is prone to "cold welding" or adhesive wear with the mating material at high friction temperatures, causing material transfer and surface failure. To overcome this limitation, researchers have developed various surface strengthening techniques, including thermal oxidation, laser cladding, plasma spraying, physical / chemical vapor deposition (PVD / CVD) and ion implantation, etc. by building high-hardness coatings (such as titanium oxide, titanium nitride, diamond-like carbon, etc.) on the surface to improve wear resistance. However, these techniques can usually only treat the surface of the component within a few millimeters, and the process is complex, costly, and difficult to achieve uniform coating coverage on complex-shaped components, making repair difficult and limiting its engineering applicability.

[0004] To further improve the overall wear resistance and comprehensive performance of titanium alloy, particle reinforced titanium matrix composite has become an important development direction. The current mainstream preparation methods are in-situ synthesis technologies, including casting, powder metallurgy, self-propagating high-temperature synthesis, mechanical alloying and laser deposition, which can be divided into solid-solid, solid-liquid and gas-solid reaction methods according to the reaction type, among which the solid-solid reaction method such as spark plasma sintering and reaction hot pressing is the most widely used. However, a single method is usually difficult to prepare a product with comprehensive matching of size, shape and performance at one time, and often needs to be assisted by subsequent processing to obtain a usable component. In addition, due to the introduction of high-hardness ceramic reinforcing phases (such as carbides and oxides), the deformation resistance of such composites is large and the room temperature plasticity is poor, which significantly increases the difficulty of hot working, especially the forming of complex profile workpieces. During the mixing of the matrix alloy and the ceramic, problems such as agglomeration of ceramic particles often occur, which affects the composition distribution and printing quality. Therefore, future research on the processing technology of titanium matrix composites needs to be further strengthened to promote its engineering application and industrialization. SUMMARY

[0005] To solve the problems in the background art, the present application provides a high wear resistance additive forming titanium matrix composite material and its preparation method and application, which includes two stages, the first stage is the composite material preparation stage, and the second stage is the laser selective melting forming stage. The material is surface modified by depositing an amorphous ceramic film on the surface of the titanium alloy powder to improve its flowability and oxidation resistance. Then, the selective melting technology is used to induce in-situ reaction of Ti elements in titanium alloy and B, C or N elements in amorphous ceramic film to generate nano-reinforced phases (one or more of TiC, TiB and TiN), and realize uniform and dispersed distribution of bulk titanium matrix composite. By accurately controlling the thickness and quality of the amorphous ceramic film, the number and size of the reinforcing phase can be controlled.

[0006] The technical scheme adopted by the present application is:

[0007] I. A high wear resistance additive forming titanium matrix composite material

[0008] The high wear resistance additive forming titanium matrix composite material is mainly composed of a matrix and an amorphous ceramic film, and the mass fraction of each component of the high wear resistance additive forming titanium matrix composite material is:

[0009] Matrix: 97.0-99.8%;

[0010] Amorphous ceramic film: 0.2-3.0%.

[0011] The base body is a titanium alloy system powder, the titanium alloy system powder is one or a combination of more of TA1, TA15, TC4, TA18, and TC21; and the amorphous ceramic film is one or a combination of more of TiB2, B4C, and BN.

[0012] II. Preparation method of high wear resistance additive forming titanium-based composite material

[0013] Composite material preparation stage:

[0014] S1: The titanium alloy powder is subjected to sufficient drying treatment in a vacuum drying box to remove the physical adsorption water on the titanium alloy powder, and dry titanium alloy powder is obtained.

[0015] S2: The surface of the dry titanium alloy powder is first subjected to in-situ plasma etching cleaning, and then ceramic particles are put in according to a certain proportion, and a dense amorphous ceramic film is deposited by using a thin film deposition technology, and titanium alloy composite material powder with an amorphous ceramic film on the surface is obtained.

[0016] S3: The titanium alloy composite material powder with the amorphous ceramic film on the surface is sequentially subjected to sieving and drying, and titanium-based composite material powder is obtained.

[0017] In the step S1, the titanium alloy powder is one or a combination of more of TA1, TA15, TC4, TA18, and TC21.

[0018] In the step S2, the ceramic particles are one or a combination of more of B4C, TiB2, and BN, and the mass of the ceramic particles is 0.2-3.1% of the mass of the dry titanium alloy powder.

[0019] In the step S2, the thickness of the amorphous ceramic film is 10-300 nm, the in-situ plasma etching cleaning is performed in an argon gas chamber, and the thin film deposition technology is one of physical vapor deposition (PVD) and chemical vapor deposition (CVD).

[0020] The particle size of the titanium-based composite material powder obtained after sieving in the step S3 is 15-53 µm.

[0021] III. Application of high wear resistance additive forming titanium-based composite material

[0022] In the application of additive manufacturing of titanium alloy material.

[0023] IV. Additive manufacturing method of titanium alloy material of high wear resistance additive forming titanium-based composite material

[0024] Laser selective melting forming stage:

[0025] 1) Application of three-dimensional software to build the required part model, and the part model is layered according to the requirements of layered analysis;

[0026] 2) Use of selective laser melting technology, i.e. laser powder bed fusion to additively manufacture titanium-based composite powder with amorphous ceramic film on the surface. The layered part model is imported into the laser additive manufacturing equipment, and the titanium-based composite powder is printed by laser powder bed fusion according to the set process parameters, to obtain in-situ titanium-based composite bulk;

[0027] 3) Microstructure characterization and performance verification of the prepared in-situ titanium-based composite bulk.

[0028] In step 2), the laser power used in the laser powder bed fusion is set between 150-200W, the scanning speed is kept between 1200-1800mm / s, and the layer thickness is set to 20-40µm; the oxygen content of the laser powder bed fusion is controlled below 0.200%; the substrate preheating temperature of the laser powder bed fusion is set to 120-180℃.

[0029] Through amorphous layer modification on the surface of the particles, the moisture resistance, flowability, compactness, dispersibility, and cohesion of the printing powder can be greatly improved, the reflectivity can be reduced, the oxidation can be reduced, the crystal boundary can be made smaller and more uniform, and the inclusions can be reduced.

[0030] In the laser powder bed fusion process of the titanium-based composite powder, titanium elements will react with B, C, N and other elements in the amorphous ceramic: Ti+TiB2→TiB, or Ti+B4C→TiB+TiC, or Ti+BN→TiB+TiN, and then introduce TiB, TiN whiskers or TiC reinforcing phase into the titanium alloy matrix. The reinforcing phase is uniformly distributed in the titanium solid solution matrix, which can form a low interface energy coherent interface with the matrix.

[0031] The ceramic reinforcing phase is introduced into the titanium-based composite powder system. Ceramic particles usually have high hardness, high elastic modulus, and high melting point. Uniformly distributed ceramic particles can significantly change the solidification path of the matrix and compounds, and can refine the grains as a heterogeneous nucleating agent, while significantly improving the thermal stress distribution during rapid solidification and inhibiting the generation of thermal cracks, thereby improving the formability and heat resistance of the alloy.

[0032] By adding ceramic reinforcing phase in-situ in the titanium alloy powder, the strength, hardness and wear resistance of the printed titanium alloy are simultaneously improved.

[0033] In the present application, different precursors are selected, a dense amorphous ceramic film is deposited on the surface of titanium alloy powder by thin film deposition technology, and Ti element in titanium alloy and B, C or N element in amorphous ceramic film are induced to react in situ by selective melting technology to generate nano-whisker strengthening phase (one or more of TiC, TiB and TiN), which is uniformly dispersed in bulk titanium-based composite material. By accurately controlling the thickness and quality of the amorphous ceramic film, the number and size of the strengthening phase can be controlled. The introduction of the amorphous ceramic film will significantly improve the flowability and oxidation resistance of the additive manufacturing titanium alloy powder. The in-situ self-grown ceramic reinforced titanium-based composite material prepared by additive manufacturing is crack-free, high in hardness and good in wear resistance, and is suitable for use in harsh working conditions.

[0034] The present application has the following beneficial effects:

[0035] The present application provides a high wear-resistant additive forming titanium-based composite material and a preparation method thereof. The present application combines thin film deposition technology and additive manufacturing technology to realize the preparation of nano-whisker reinforced titanium-based composite material by in-situ reaction. The bulk titanium-based composite material prepared by the method has excellent comprehensive mechanical properties and has wide application prospects in the fields of aerospace, transportation and the like.

[0036] The titanium alloy powder prepared in the present application has good flowability and strong oxidation resistance. The in-situ self-grown nano-whisker reinforced titanium-based composite material prepared by additive manufacturing has high strength / hardness, good wear resistance and high forming quality, and is suitable for use in extremely harsh working conditions. BRIEF DESCRIPTION OF DRAWINGS

[0037] Figure 1 The present application provides a high wear-resistant additive forming titanium-based composite material and a preparation method thereof. The present application combines thin film deposition technology and additive manufacturing technology to realize the preparation of nano-whisker reinforced titanium-based composite material by in-situ reaction. The bulk titanium-based composite material prepared by the method has excellent comprehensive mechanical properties and has wide application prospects in the fields of aerospace, transportation and the like.

[0038] Figure 2 The present application provides a high wear-resistant additive forming titanium-based composite material and a preparation method thereof. The present application combines thin film deposition technology and additive manufacturing technology to realize the preparation of nano-whisker reinforced titanium-based composite material by in-situ reaction. The bulk titanium-based composite material prepared by the method has excellent comprehensive mechanical properties and has wide application prospects in the fields of aerospace, transportation and the like.

[0039] Figure 3 The present application provides a high wear-resistant additive forming titanium-based composite material and a preparation method thereof. The present application combines thin film deposition technology and additive manufacturing technology to realize the preparation of nano-whisker reinforced titanium-based composite material by in-situ reaction. The bulk titanium-based composite material prepared by the method has excellent comprehensive mechanical properties and has wide application prospects in the fields of aerospace, transportation and the like.

[0040] Figure 4 The present application provides a high wear-resistant additive forming titanium-based composite material and a preparation method thereof. The present application combines thin film deposition technology and additive manufacturing technology to realize the preparation of nano-whisker reinforced titanium-based composite material by in-situ reaction. The bulk titanium-based composite material prepared by the method has excellent comprehensive mechanical properties and has wide application prospects in the fields of aerospace, transportation and the like.

[0041] Figure 5For the friction performance map of the printed titanium-based composite material in Example 1, (a) is the scratch profile morphology image of the printed titanium-based composite material after friction test after adding 1% mass fraction of TiB2 (the thickness of the amorphous TiB2 ceramic film is 200 nm); (b) is the high-low fluctuation change of the scratch profile along the X direction of the printed titanium-based composite material after friction test after adding 1% mass fraction of TiB2;

[0042] Figure 6 For the friction performance map of the printed TC4 powder without TiB2 amorphous ceramic film coating, (a) is the friction scratch profile morphology image of the printed TC4 powder without TiB2 amorphous ceramic film coating; (b) is the high-low fluctuation change of the friction scratch profile along the X direction of the printed TC4 powder without TiB2 amorphous ceramic film coating;

[0043] Figure 7 For the printed morphology map of the TiB2 / TC4 composite material in Comparative Example 2. DETAILED DESCRIPTION

[0044] The application will be further described in detail below in combination with the drawings and specific examples.

[0045] The embodiments of the application are as follows: Example 1:

[0046] As shown in Figure 1 , the preparation process of the high-wear-resistance additive formed titanium-based composite material is as follows:

[0047] Step 1: Select spherical TC4 powder with a particle size distribution of 15-53 μm, and place the spherical TC4 powder in a vacuum drying box and dry at 120°C for at least 12 hours to completely remove the physically adsorbed water.

[0048] Step 2: Reactor loading

[0049] The treated dry powder is loaded into the deposition chamber of the special fluidized bed sputtering film coating equipment.

[0050] Step 3: High vacuum and preheating

[0051] The deposition chamber is pumped to high vacuum (background vacuum ≤ 5.0 × 10⁻ 4 Pa). The heater is turned on, the powder is preheated to the predetermined deposition temperature (120°C), and a small amount of high-purity Ar gas (Ar gas is 99.999% high-purity argon gas, pressure 10 Pa) is introduced, the fluidization system is started to begin preliminary fluidization, and the powder is uniformly heated during preheating.

[0052] Step 4: In-situ plasma etching cleaning

[0053] The deposition chamber is connected to Ar gas, and the pressure is adjusted to the working pressure required for fluidization (10 Pa). Turn on the fluidizing gas to keep the powder bed in a stable fluidized state. Turn on the radio frequency (RF) plasma power source (or directly use the power source of the sputtering target) to generate Ar plasma and bombard the surface of the powder in the fluidized state for 10-20 minutes. This step can effectively remove the trace amounts of oxides and adsorbates on the surface of the powder, significantly improving the adhesion of the thin film.

[0054] Step 5: Thin film deposition

[0055] A TiB2 ceramic target with a stoichiometric ratio of 1:2 (sintered target) is selected and sputtering is started. First, maintain a stable Ar gas flow and working pressure to ensure continuous and stable fluidization of the powder, then turn on the magnetron sputtering power source and use the radio frequency (RF) power source. Gradually increase the power to the preset value to generate a stable and uniform plasma, set the power to 200 W, accurately control the deposition temperature to 120°C, and the chamber pressure to 0.8 x 10 -7 Torr, and the deposition time is 5h. The atoms and atomic groups in the TiB2 target are sputtered and deposited on the surface of the continuously rolling titanium powder.

[0056] Step 6: Cooling and sampling

[0057] Turn off the magnetron sputtering power source and the heater in sequence, continue to flow Ar gas and maintain fluidization, and let the powder cool down to room temperature under the protection of inert gas to prevent high-temperature powder from contacting oxygen in the air and being oxidized. The average thickness of the amorphous TiB2 ceramic thin film deposited on the surface of the TC4 particles is 200 nm, and the mass fraction is 1%. Then open the chamber, take out the coated powder, and store it in a desiccator.

[0058] Step 7: Additive manufacturing of the coated titanium-based composite material powder

[0059] First, use the laser powder bed fusion equipment to spread the powder, then print it. Use a one-way scanning strategy, set the powder layer thickness to 30µm, the laser power to 180W, the scanning speed to 1250mm / s, the scanning interval to 90µm, the angle increment to 67°, and the area overlap to 0.13mm. Use argon gas to protect during the forming process, the oxygen content in the argon atmosphere is ≤0.200%, and the substrate preheating temperature during the forming process is 180°C. After printing is completed, the substrate is cooled to room temperature and then removed.

[0060] Step 8: Microstructure characterization and performance verification of the printed TiB2 / TC4 titanium-based composite material block

[0061] As shown in Figure 2 the microstructure morphology diagram of the TC4 after thin film deposition, the titanium-based composite material powder prepared by the present application has good sphericity; asFigure 3 As shown in (a), (b), (c) and (d), the additive manufacturing titanium alloy bulk morphology, i.e. the printed titanium alloy bulk has no visible cracks with good formability; as shown in (a) and (b), the friction performance diagram of the printed titanium-based composite material shows that the scratch of the sample after adding ceramic particles is shallower, showing strong wear resistance. Figure 4 As shown in (a), (b), (c) and (d), the in-situ reaction generated TiB exists in the form of nanorod whiskers; as shown in (a) and (b), the friction performance diagram of the printed titanium-based composite material shows that the scratch of the sample after adding ceramic particles is shallower, showing strong wear resistance. Figure 5 As shown in (a), (b), (c) and (d), the additive manufacturing titanium alloy bulk morphology, i.e. the printed titanium alloy bulk has no visible cracks with good formability; as shown in (a) and (b), the friction performance diagram of the printed titanium-based composite material shows that the scratch of the sample after adding ceramic particles is shallower, showing strong wear resistance. Example 2:

[0062] Step 1: Selecting industrial pure titanium (TA1) powder with particle size distribution of 15-53 μm, placing the industrial pure titanium (TA1) powder in a vacuum drying box, drying at 110°C for at least 15 hours to completely remove the physically adsorbed water.

[0063] Step 2: Reactor loading

[0064] The treated dry powder is loaded into the deposition chamber of a special fluidized bed PVD equipment.

[0065] Step 3: High vacuum and preheating

[0066] The deposition chamber is pumped to high vacuum (background vacuum ≤ 5.0 × 10⁻ 4 Pa). Turn on the heater and heat the powder to the predetermined deposition temperature (150°C). At the same time, a small amount of high-purity Ar gas (Ar gas is 99.999% high-purity argon, pressure 10 Pa) is introduced, the fluidization system is started to begin preliminary fluidization, and the powder is uniformly heated during preheating.

[0067] Step 4: In-situ plasma etching cleaning

[0068] Introduce Ar gas into the deposition chamber and adjust the Ar gas pressure to the working pressure required for fluidization (15 Pa). Turn on the fluidization gas to make the powder bed in a stable fluidized state. Then turn on the radio frequency (RF) plasma power to generate Ar plasma. The powder in the fluidized state is bombarded and cleaned for 15-25 minutes. This step can effectively remove the very thin oxide layer formed on the surface of the powder during transportation and preheating, significantly improving the adhesion between the film and the substrate.

[0069] Step 5: BN thin film deposition

[0070] Use a BN ceramic target (sintered target) with a stoichiometric ratio close to 1:1, and turn on the sputtering. First, maintain a stable Ar gas flow and working pressure to ensure continuous and stable fluidization of the powder. Then turn on the radio frequency (RF) power connected to the BN target, gradually and slowly increase the power to the preset value, and generate a stable and uniform plasma. Set the power to 250 W, accurately control the deposition temperature to 150°C, and the cavity pressure to 0.65 × 10-7 Torr, deposition time 2h. Atoms and atomic groups in the BN target were sputtered out and deposited on the surface of the continuously rolling titanium powder. The deposition temperature, sputtering power, working pressure and deposition time were precisely controlled, and low temperature (<150℃) was the key to inhibit atomic diffusion and form amorphous BN.

[0071] Step 6: Cooling and sampling

[0072] The sputtering power and the heater were turned off in sequence, and the Ar gas was continuously introduced and kept fluidized to prevent the high-temperature powder from being oxidized by contacting oxygen in the air. Then the chamber was opened, the coated powder was taken out and placed in a desiccator for storage.

[0073] Step 7: The thickness of the amorphous BN ceramic film deposited on the surface of TA1 particles was 90 nm, and the mass fraction was 0.3%;

[0074] Step 8: Powder bed fusion printing

[0075] First, the powder was laid by using the laser powder bed fusion equipment, and then printing was performed. The powder layer thickness was set to 40µm, the laser power was set to 160W, the scanning speed was set to 1200mm / s, the scanning interval was 60µm, the angle increment was 67°, and the area overlap was set to 0.13mm. The forming process was protected by argon, and the oxygen content in the argon atmosphere was ≤0.200%, and the substrate preheating temperature during the forming process was 200℃. After printing, the substrate was taken out after cooling to room temperature.

[0076] In this embodiment 2, in-situ reaction of Ti+BN→TiB+TiN occurred during additive manufacturing, so two kinds of reinforcing phases: TiB and TiN can be introduced in-situ in the titanium matrix. The whiskers TiB and TiN synergistically work together to avoid the limitations of one kind of whisker and achieve further improvement of wear resistance.

[0077] Comparative Example 1:

[0078] For TC4 powder without TiB2 ceramic coating, the TC4 powder was sieved and dried before printing. The printing parameters were the same as in Example 1, i.e. using a one-way scanning strategy, the powder layer thickness was 30µm, the laser power was 180W, the scanning speed was 1250mm / s, the scanning interval was 90µm, the angle increment was 67°, and the area overlap was set to 0.13mm. The forming process was protected by argon, and the oxygen content in the argon atmosphere was ≤0.200%, and the substrate preheating temperature during the forming process was 180℃. After printing, the substrate was taken out after cooling.

[0079] The friction performance of TC4 powder coated with TiB2-free amorphous ceramic film after printing was as follows Figure 6The results of (a) and (b) are shown. The titanium alloy without TiB2addition has poor wear resistance and deep scratches, which can be illustrated by comparison with Example 1, and TiB2plays a key role in improving the wear resistance of the titanium alloy.

[0080] Comparative Example 2:

[0081] The deposition process was changed to increase the thickness of the amorphous ceramic film on the surface of the TC4 titanium alloy particles to 500 nm. A TiB2ceramic target (sintered target) with a stoichiometric ratio of 1:2 was selected, and sputtering was started. The deposition process was controlled to deposit an amorphous TiB2ceramic film on the surface of the TC4 particles. First, a stable Ar gas flow and working pressure were maintained to ensure continuous and stable fluidization of the powder. Then, the magnetron sputtering power was turned on, and an RF power source was used. The power was gradually increased to the preset value to generate a stable and uniform plasma. The power was set to 200 W, the deposition temperature was accurately controlled to 120℃, the cavity pressure was 0.8×10 -7 Torr, and the deposition time was 12 h. The mass fraction of the amorphous ceramic film after deposition was 5%.

[0082] The TC4 powder modified with a higher thickness (higher mass fraction) amorphous ceramic film was printed. The printing parameters were also the same as in Example 1, i.e., a unidirectional scanning strategy was used, the powder layer thickness was 30 µm, the laser power was 180 W, the scanning speed was 1250 mm / s, the scanning interval was 90 µm, the angle increment was 67°, and the area overlap was set to 0.13 mm. Argon gas was used to protect the forming process, and the oxygen content in the argon atmosphere was ≤0.200%. The substrate preheating temperature during the forming process was 180℃. After printing, the sample was cooled and removed.

[0083] Figure 7 The printing morphology of the TiB2 / TC4 composite material in this comparative example is shown. As can be seen from the figure, the TiB2 / TC4 titanium-based composite material printed in this comparative example has visible cracks, which indicates that if the concentration of hard and brittle TiB particles generated in situ is too high, the micro stress will be too large, the sample will become brittle, and then macro cracks will appear, affecting the printing formability.

[0084] The above examples are used to explain and illustrate the present application, but are not limiting to the present application. Any modifications and changes made to the present application within the spirit and protection scope of the claims fall within the protection scope of the present application.

Claims

1. A high-wear-resistant additively formed titanium-based composite material, characterized in that: The high wear-resistant additively formed titanium-based composite material is mainly composed of a matrix and an amorphous ceramic film. The mass fraction of each component of the high wear-resistant additively formed titanium-based composite material is as follows: Matrix: 97.0-99.8%; Amorphous ceramic thin films: 0.2-3.0%; The substrate is a titanium alloy powder, which is one or more of TA1, TA15, TC4, TA18, and TC21; the amorphous ceramic film is one or more of TiB2, B4C, and BN. The high wear-resistant additively formed titanium-based composite material is prepared according to the following method: S1: The titanium alloy powder is thoroughly dried in a vacuum drying oven to remove the physically adsorbed water on the titanium alloy powder and obtain dry titanium alloy powder. S2: First, the surface of the dry titanium alloy powder is cleaned by in-situ plasma etching, then ceramic particles are placed in it, and an amorphous ceramic film is deposited using thin film deposition technology to obtain titanium alloy composite powder with an amorphous ceramic film on the surface. S3: The titanium alloy composite material powder with an amorphous ceramic film on its surface is sieved and dried sequentially to obtain titanium-based composite material powder.

2. A method for preparing the high wear-resistant additively formed titanium-based composite material according to claim 1, characterized in that: The method includes: S1: The titanium alloy powder is thoroughly dried in a vacuum drying oven to remove the physically adsorbed water on the titanium alloy powder and obtain dry titanium alloy powder. S2: First, the surface of the dry titanium alloy powder is cleaned by in-situ plasma etching, then ceramic particles are placed in it, and an amorphous ceramic film is deposited using thin film deposition technology to obtain titanium alloy composite powder with an amorphous ceramic film on the surface. S3: The titanium alloy composite material powder with an amorphous ceramic film on its surface is sieved and dried sequentially to obtain titanium-based composite material powder.

3. The method for preparing a high wear-resistant additively formed titanium-based composite material according to claim 2, characterized in that: In step S1, the titanium alloy powder is one or more of TA1, TA15, TC4, TA18, and TC21.

4. The method for preparing a high wear-resistant additively formed titanium-based composite material according to claim 2, characterized in that: In step S2, the ceramic particles are one or more of B4C, TiB2, and BN, and the mass of the ceramic particles is 0.2-3.1% of the mass of the dry titanium alloy powder.

5. The method for preparing a high wear-resistant additively formed titanium-based composite material according to claim 2, characterized in that: In step S2, the thickness of the amorphous ceramic thin film is 10nm-300nm, the in-situ plasma etching and cleaning is performed in a chamber filled with argon gas, and the thin film deposition technique is one of physical vapor deposition or chemical vapor deposition.

6. The method for preparing a high wear-resistant additively formed titanium-based composite material according to claim 2, characterized in that: The particle size of the titanium-based composite material powder obtained after sieving in step S3 is 15~53µm.

7. The application of the high wear-resistant additively formed titanium matrix composite material according to claim 1 or the high wear-resistant additively formed titanium matrix composite material prepared by any of the preparation methods according to claims 2-6, characterized in that: Applications of titanium alloy materials in additive manufacturing.

8. A method for additive manufacturing of titanium alloy materials applied to the high wear-resistant additively formed titanium matrix composite material according to claim 1 or the high wear-resistant additively formed titanium matrix composite material prepared by any of the preparation methods according to claims 2-6, characterized in that: 1) Use 3D software to construct the required part model, and then process the part model into layers according to the requirements of layered analysis; 2): The layered part model is imported into the laser additive manufacturing equipment, and the titanium-based composite material powder is printed by laser powder bed melting according to the set process parameters to obtain an in-situ self-generated titanium-based composite material block; 3): The microstructure of the prepared in-situ self-generated titanium-based composite material block was characterized and its performance was verified.

9. The additive manufacturing method for titanium alloy materials according to claim 8, characterized in that: In step 2), the laser power used for laser powder bed melting is set between 150 and 200W, the scanning speed is maintained between 1200 and 1800 mm / s, and the layer thickness is set between 20 and 40 µm; the oxygen content of the laser powder bed melting is controlled below 0.200%.

Citation Information

Patent Citations

  • Titanium powder coated with oxygen impurity adsorbent and preparation method of titanium powder

    CN112605382A

  • Ceramic particle reinforced titanium-based composite material for 3D printing and preparation method of ceramic particle reinforced titanium-based composite material

    CN114523103A

  • Titanium-based composite material with adjustable and controllable reinforced phase structure and preparation method of titanium-based composite material

    CN120193178A